Downsizing and Productivity Gains in the Public and Private Sectors of Colombia - Rama, Martín; Newman, Constance (World Bank, Washington, DC, 2013)
Public sector restructuring, including labor downsizing, has been one of the main areas of policy activism in developing countries, and transition economies. But little is known about its actual effects. The authors use panel data on Colombian enterprises spanning more than one decade, to assess the impact on several productivity indicators. The results suggest that the productivity gains from downsizing, are larger in state-owned enterprises than in private enterprises. While the increase in value added per worker is similar in both cases, state-owned enterprises experience an increase in total value added, and in value added per unit of capital, whereas both indicators decline in private enterprises. The difference, which could simply reflect the larger extent of initial inefficiency in state-owned enterprises, does not appear to depend on the degree of competition in product markets.